2019
DOI: 10.3390/e21020128
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Complex Networks Using Entropy-Degree Diagrams: Unveiling Changes in Functional Brain Connectivity Induced by Ayahuasca

Abstract: Open problems abound in the theory of complex networks, which has found successful application to diverse fields of science. With the aim of further advancing the understanding of the brain's functional connectivity, we propose to evaluate a network metric which we term the geodesic entropy. This entropy, in a way that can be made precise, quantifies the Shannon entropy of the distance distribution to a specific node from all other nodes. Measurements of geodesic entropy allow for the characterization of the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
58
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 32 publications
7
58
0
5
Order By: Relevance
“…Tryptamine psychedelics such as psilocybin are known to alter perception, mood, and a host of cognitive processes (Nichols 2004) and have been indicated for the treatment of mood disorders (Carhart-Harris et al 2018;Griffiths et al 2006;Viol et al 2019). Additionally, classical serotonergic hallucinogens such as LSD or psilocybin are considered physiologically safe and do not produce dependence or addiction (Nichols 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Tryptamine psychedelics such as psilocybin are known to alter perception, mood, and a host of cognitive processes (Nichols 2004) and have been indicated for the treatment of mood disorders (Carhart-Harris et al 2018;Griffiths et al 2006;Viol et al 2019). Additionally, classical serotonergic hallucinogens such as LSD or psilocybin are considered physiologically safe and do not produce dependence or addiction (Nichols 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent neuroimaging studies have explored the acute effects of psychedelics on functional organization of human brain networks (Carhart-Harris et al, 2012; Carhart-Harris et al, 2016b; Palhano-Fontes et al, 2015; Roseman et al, 2014; Viol et al, 2017, 2019), with reports of increased functional integration at the global brain level (Petri et al, 2014; Tagliazucchi et al, 2016; Viol et al, 2017), and connectivity increases primarily affecting the primary visual cortex and frontal areas (Carhart-Harris et al, 2016b; De Araujo et al, 2012). Only one study has reported salience network connectivity decreases under acute conditions (Lebedev et al, 2015), whereas most studies report decreased connectivity in important hubs of the default mode network, such as the posterior cingulate cortex (Carhart-Harris et al, 2012; Lebedev et al, 2015; Palhano-Fontes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the appropriate ensemble description in hand, thermodynamic properties, such as temperature, Helmholtz free energy, and entropy can be used to capture the macroscopic characteristics of the network [ 24 , 25 ]. Here the partition function depending on temperature and the energy states plays a powerful role in describing the behaviour of the network degree distribution [ 26 ]. The variance of degree distribution and the decomposition of entropy on each node effectively are salient features that can be used in identifying the influential regions in the brain [ 27 ].…”
Section: Introductionmentioning
confidence: 99%